2009
DOI: 10.1016/j.foodres.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrophobic plasticizers on functional properties of gelatin-based films

Abstract: a b s t r a c tThe aim of this study was the production and characterization of gelatin-based films using hydrophobic plasticizers derived from citric acid and soy lecithin as emulsifier. The films were characterized as to their mechanic properties, permeability to water vapor, opacity, morphology and possible interactions using Fourier transform infrared spectroscopy. Tensile strength values (TS) varied from 36 to 103 MPa, however, the increase in the concentration of plasticizers (acetyltributyl citrate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 35 publications
5
74
0
3
Order By: Relevance
“…The infrared spectra of CMC, gelatin and starch, and their blends are represented in Figure 2. The spectrum of CMC, starch and gelatin alone were similar to previous reported in the literature [15,22,23] . For CMC characteristic band were observed at 1587 cm -1 (stretching of C=O), 1415 cm -1 (CH2 carboxylic groups), 1322 cm -1 (absorption of CH2) e 1051 cm -1 (stretching of C-O), consistent with previous data reported [22] .…”
Section: Ftir Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…The infrared spectra of CMC, gelatin and starch, and their blends are represented in Figure 2. The spectrum of CMC, starch and gelatin alone were similar to previous reported in the literature [15,22,23] . For CMC characteristic band were observed at 1587 cm -1 (stretching of C=O), 1415 cm -1 (CH2 carboxylic groups), 1322 cm -1 (absorption of CH2) e 1051 cm -1 (stretching of C-O), consistent with previous data reported [22] .…”
Section: Ftir Analysissupporting
confidence: 88%
“…The intense bands between 1700 and 1600 cm -1 and between 1600 and 1500 cm -1 , are known, respectively, as bands of amide I and amide II. Amide III, with bands between 1200 and 1400 cm -1 , represent components of the extension of C-N and N-H and absorptions resulting from the vibrations of groups C-H2 of the glycine and proline [23] . Starch oral film also presents similar FTIR spectra from the one previous presented [15] .…”
Section: Ftir Analysismentioning
confidence: 99%
“…The use of glycerol as plasticizer produced films with maximum of 52.3% and 41.2% of elongation, when associated with yucca extract and lecithin, respectively (Table 1), being higher than the values observed when these surfactants were used in combination with hydrophobic plasticizers [15,16] . Higher elongations, compared to those obtained in this work, have been reported previously in the literature, combining gelatin and glycerol, as plasticizer agent, for film production without the addition of surfactants [5,23] .…”
Section: Mechanical Propertiesmentioning
confidence: 85%
“…The dry powder is the form used for animal feed [11][12][13][14] . Andreuccetti et al [15,16] produced films based on gelatin containing hydrophobic plasticizers derived from citric acid and natural surfactants (lecithin or Yucca schidigera extract), by casting. The films showed good mechanical resistance and low permeability to water vapor, however in the formulations studied, the elongation was low indicating that the plasticizers, or surfactants, have not been properly incorporated into the protein matrix, producing films with low elongation values.…”
Section: Introductionmentioning
confidence: 99%
“…However the DTG had shown greater plasticizer efficiency, followed by GLY and ETG, while a counter effect was observed with the addition of PPG. Andreuccetti et al (2009) determined the effect of hydrophobic plasticizers derived from citric acid (tributyl citrate, acetyltributyl citrate, triethyl citrate, acetyltriethyl citrate) on the functional properties of gelatin-based films. They found that the addition of ester citrate derivatives in gelatin-based film formulations proved feasible, generating flexible materials.…”
Section: Film Additivementioning
confidence: 99%